The Relationship Between Emotional Intelligence and Learning Outcomes of Grade II Elementary School Students - Wahyuni, Tri; Amriyah, Chairul; Afriyadi, Muhammad Muchsin (Program Studi PGMI, Universitas Al Falah As Sunniyah Kencong Jember, 2025)
This study aims to find the relationship between emotional intelligence and learning outcomes of grade III elementary school students. The research method used in this study uses a quantitative approach with a correlation research type. The population in this study were all grade II I of Muhammadiyah Sukajawa Elementary School, Central Lampung, totaling 20 students. The data collection tools used were questionnaires to find emotional intelligence data and tests to find learning outcome data. The prerequisite tests used were normality tests and linearity tests. The data analysis technique in this study used the Pearson correlation test (product moment correlation). Based on the research, the results showed that there is a relationship between students' emotional intelligence and the learning outcomes of grade III students of Muhammadiyah Elementary School Sukajawa, Central Lampung.